2021
DOI: 10.7759/cureus.13716
|View full text |Cite
|
Sign up to set email alerts
|

Can Targeting Iron Help in Combating Chronic Pseudomonas Infection? A Systematic Review

Abstract: Cystic fibrosis is an autosomal recessive disorder caused by a mutation in genes for cystic fibrosis transmembrane conductance regulator (CFTR) protein. CFTR gene is responsible for the production of sweat, digestive fluids, and mucus, and any mutation in this would lead to the thickening of these secretions. Cystic fibrosis is a multi-organ disorder, but 80% of patients suffer from respiratory problems due to chronic infections most commonly caused by Pseudomonas aeruginosa (P. aeruginosa). Eradication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Updated AmpliSeq panels or whole-genome sequencing, along with targeted experimental studies, could be used to test the hypothesis that variation in these genes plays a role in disease progression. Multiple studies have shown competition for iron to be key for the survival and virulence of many of the pathogens that reside in the CF lung, including Pa [59, 60]. We also found that SNVs predictive of lung function decline are enriched in genes involved in stress/metabolism.…”
Section: Discussionmentioning
confidence: 52%
“…Updated AmpliSeq panels or whole-genome sequencing, along with targeted experimental studies, could be used to test the hypothesis that variation in these genes plays a role in disease progression. Multiple studies have shown competition for iron to be key for the survival and virulence of many of the pathogens that reside in the CF lung, including Pa [59, 60]. We also found that SNVs predictive of lung function decline are enriched in genes involved in stress/metabolism.…”
Section: Discussionmentioning
confidence: 52%
“…The management of pulmonary infections, and Bcc infection specifically, requires that clinicians assess each person individually, taking into account symptomatic changes, previous clinical responses and their own experiences [3]. Evidence from the literature, which to date is largely founded on in vitro studies or case reports, supports that cefiderocol is an antibiotic that appears to expand the treatment options for CF patients colonized with MDR Gram-negative bacilli [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Updated AmpliSeq panels or whole-genome sequencing, along with targeted experimental studies, could be used to test the hypothesis that variation in these genes plays a role in disease progression. Multiple studies have shown competition for iron to be key for the survival and virulence of many of the pathogens that reside in the CF lung, including Pa (Bouvier 2016, Firoz, Haris et al 2021). We also found that SNVs predictive of lung function decline are enriched in genes involved in stress/metabolism.…”
Section: Discussionmentioning
confidence: 99%